Tourism and Women Employment Generation in Nepal - Acharya, Krishna Raj (Humanities and Social Sciences Journal, 2021)
The objective of this research paper was to explore and analyze the money-making activities of women in tourism industry of Nepal in Pashupati Nath Area. A descriptive study was carried out among 70 respondents from July 15, 2019 to July 24, 2020 in the Pashupatinath area, using a convenience sampling method. Data were obtained from face-to-face interviews, questionnaire, and observation. A fair investment in business activities was found in the study area. Most of the items were bought in Nepal, India, and China. Rudrachhyas were found as the main items that were sold in highest number. The lack of co-ordination from the local stakeholders was observed as a major problem faced by the business people. The study suggests that there should be an effective co- ordination from the related stakeholders for the sustainability of tourism and business activities. The stakeholders’ involvement could take place in several ways, such as providing financial resources, training and education, cost sharing, management of spill over, and reducing disparities. These overall activities may help to attract more customers, finally help to sustain businesses, and increase the economic scope of the study area. Income earned by women before and after working in this sector is statistically significant. P- Value is .001 < .01 indicates the same fact. It rejects the null hypothesis there is no difference in mean income received by women entrepreneurs / employees in their respective works. Now there is a space to pronounce that there is difference in income and alternative hypothesis is true. In the study, it was found that employment can change their economic, social, religious and political access with a feeling of a reputed citizen in a nation.